Proceedings of the Ocean Drilling Program 1996
DOI: 10.2973/odp.proc.sr.151.137.1996
|View full text |Cite
|
Sign up to set email alerts
|

Recent to Middle Miocene Diatom Productivity at Site 907, Iceland Plateau

Abstract: Surface water productivity at Ocean Drilling Program Site 907 has been assessed from total diatom abundance and Chaetoceros resting spore frequency. The sediments are divided into four intervals based on relative diatom abundance. Intervals 1 and 4 are mainly barren of diatoms. Interval 2 shows a highly fluctuating abundance pattern, whereas Interval 3 is a biosilicarich middle to late Miocene (13.7-10.1 Ma) sediment containing abundant diatoms dominated by Chaetoceros resting spores. Resting spores of Chaetoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…The decrease in Atlantic overturning we observe here during interglacial stages is corroborated by studies of siliceous microfossils (e.g., Koç and Scherer, 1996;Stabell and Koç, 1996). These authors concluded based on the absence of production of silica in the surface waters of the GIN seas relative to the region south of Iceland (Koç and Flower, 1998;Koç et al, 1999) that a strong front must have existed near the Greenland-Scotland Ridge during most of the interglacials of the early to mid-Pleistocene (summarized by Raymo et al, 2004).…”
Section: Resultssupporting
confidence: 85%
“…The decrease in Atlantic overturning we observe here during interglacial stages is corroborated by studies of siliceous microfossils (e.g., Koç and Scherer, 1996;Stabell and Koç, 1996). These authors concluded based on the absence of production of silica in the surface waters of the GIN seas relative to the region south of Iceland (Koç and Flower, 1998;Koç et al, 1999) that a strong front must have existed near the Greenland-Scotland Ridge during most of the interglacials of the early to mid-Pleistocene (summarized by Raymo et al, 2004).…”
Section: Resultssupporting
confidence: 85%
“…The Middle Miocene transition (14.5-13.0 Ma) Sedimentation at Site 907 commenced shortly after the MCO and high palynomorph concentration corroborates a high primary productivity , which has also been inferred from abundant diatoms and their resting spores after 14 Ma (Stabell and Koç, 1996). However, as protoperidiniacean dinocysts are usually abundant in upwelling areas (e.g.…”
Section: Discussionsupporting
confidence: 56%
“…However, as protoperidiniacean dinocysts are usually abundant in upwelling areas (e.g. Reichart and Brinkhuis, 2003;Holzwarth et al, 2010), their low abundance during this interval in the Iceland Sea does not support substantial upwelling as suggested by Stabell and Koç (1996). Since selective degradation is excluded due to light to dark brown colors of cyst walls and no evidence of oxidative damage of Barssidinium and Cristadinium specimens encountered, the high paleoproductivity likely resulted from increased nutrient input due to enhanced chemical weathering during a much warmer and humid climate (Wan et al, 2009;Ma et al, 2011;Pound et al, 2012).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations